The current Russian model of social development, and economic growth - V V Paramonov (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2016)
Although the Article 7 of the Constitution of Russia adopted in 1993 defines the country as a social state, the contemporary social and economic situation is significantly different from this declaration. The author considers the current situation focusing on the foundations of the welfare state. The indicators of social inequality and stratification that allow to identify the country as a social state prove the widening gap between the rich and poor. In recent years, nothing has been done to achieve the more equitable distribution of income and national wealth, which led to the further growth of social inequality exceeding the global indices. The author believes that the high level of social inequality negatively affects the economic growth. Based on the studies of Russian scientists he concludes that equal distribution of income provides higher rates of economic growth and prosperity of the country. The modified theory of the factors of production explains this interconnection, and adds a few more factors, including such a specific resource as sales market, to three factors introduced by J.B. Say at the beginning of the XIX century. The huge social inequality and, consequently, a significant number of the poor deprive the country of such an important resource. To change the situation, the author proposes to return to the progressive tax scale and introduce the zero rate of income tax for the poorest groups in order to create prerequisites for the growth of consumer demand under the economic crisis.